Inhibition of thrombin on endothelium enhances recruitment of regulatory T cells during IRI and when combined with adoptive Treg transfer, significantly protects against acute tissue injury and prolongs allograft survival - Peng, Qi; Nowocin, Anna; Ratnasothy, Kulachelvy; Smith, Richard A.; Smyth, Lesley A.; Lechler, Robert I.; Dorling, Anthony; Lombardi, Giovanna (Frontiers in Immunology, 2023)
Ischemia-reperfusion injury (IRI) amplifies T cell alloimmune responses after transplantation with thrombin playing a key pro-inflammatory role. To explore the influence of thrombin on regulatory T cell recruitment and efficacy we used a well-established model of IRI in the native murine kidney. Administration of the cytotopic thrombin inhibitor PTL060 inhibited IRI, and by skewing expression of chemokines (reducing CCL2 and CCL3 but increasing CCL17 and CCL22) increased the infiltration of M2 macrophages and Tregs. When PTL060 was combined with infusion of additional Tregs, these effects were further amplified. To test the benefits of thrombin inhibition in a transplant model, BALB/c hearts were transplanted into B6 mice with or without perfusion with PTL060 in combination with Tregs. Thrombin inhibition or Treg infusion alone led to small increments in allograft survival. However, the combined therapy led to modest graft prolongation by the same mechanisms as in renal IRI; graft survival was accompanied by increased numbers of Tregs and anti inflammatory macrophages, and reduced expression of pro-inflammatory cytokines. While the grafts succumbed to rejection associated with the emergence of alloantibody, these data suggest that thrombin inhibition within the transplant vasculature enhances the efficacy of Treg infusion, a therapy that is currently entering the clinic to promote transplant tolerance.